Karakterisasi Molekuler Gen Penyandi SodC Pasteurella multocida yang Diisolasi dari Kerbau Asal Nusa Tenggara Timur (MOLECULAR CHARACTERIZATION OF SodC ENCODING GENES PASTEURELLA MULTOCIDA ISOLATED FROM BUFFALO OF EAST NUSA TENGGARA ORIGIN) - Mahindra, Ayang; Plumeriastuti, Hani; Handijatno, Didik (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Pasteurella multocida type B:2 is a bacteria which causing the disease was called Septicemia Epizooticae in ruminants, expecially cattle and buffalo. The aims of this research to determine the encoding gene SodC of Pastuerella multocida type B:2. This isolate of Pasteurella multocida type B:2  was obtained from the BBVet Denpasar, Bali that originally from East Nusa Tenggara (NTT) Indonesia. The sample was grown on Blood agar (BA). Separated colonies were grossly observed identified by macroscopicly (transparent, round and sweet-smelling) and microscopicly identified (bipolar and Gram negative), Biochemical test included Triple Sugar Iron Agar (TSIA), Urease, Simmnons Citrate Agar (SCA), Sulphid Indol Motility (SIM), Sugars Test (Sucrose, Manitol, Maltose, Glucose  and Lactose). This Isolate had been test using Polymerase Chain Reaction (PCR), the result of PCR test if Pasteurella multocida had band in 235bp. This research was continued with Sequencing test to reveal the nucleotides sequence of the encoding SodC gene in Pasteurella multocida and also the homology from Genbank or NCBI.  Result of Blasting in NCBI revealed that this encoding gene had similar nucleotides sequence with Pasteurella multocida strain 4407 (97%), Chinese 9N Pasteurella multocida strain (98%), Chinese Pasteurella multocida strain BS168 (97%), Pasteurella multocida strain EB168 China (97 %), Pasteurella multocida subsp. multocida strain CIRMBP-0884 France (97%), and Pasteurella multocida subsp. multocida strain RCAD0259 China (96%).